Genetic variation of Melia azedarach in community forests of West Java assessed by RAPD - YULIANTI YULIANTI; ISKANDAR ZULKARNAEN SIREGAR; NURHENI WIJAYANTO; IGK TAPA DARMA; DIDA SYAMSUWIDA (Biodiversitas Journal of Biological Diversity, 2011)
Yulianti, Siregar IZ, Wijayanto N, Tapa Darma IGK, Syamsuwida D (2011) Genetic variation of Melia azedarach in community forests of West Java assessed by RAPD. Biodiversitas 12: 64-69. Melia azedarach L. or mindi (local name) is one of the widely planted exotic species in Indonesia, mostly found in community forests in West Java. However, improving and increasing the productivity of mindi commmunity plantation in West Java requires information on patterns of existing genetic diversity. The present work was aimed at estimating the genetic variation of mindi by using RAPD markers. Outcome of the activities was to propose appropriate conservationand management strategies of genetic resources in order to support the establishment of seed sources. Six populations of mindi plantation in the community forests were chosen for this research, i.e Sukaraja (Bogor-1), Megamendung (Bogor-2), Bandung, Purwakarta, Sumedang and Kuningan. Five primers (OPA-07, OPY-13, OPY-16, OPA-09 and OPO-05) producing reproducible bands were analysed for 120 selected mother trees in total, in which 20 trees per locality were sampled. Data were analysed using Popgene ver 1.31, NTSYS 2.02 and GenAlEx 6.3. Based on the analysis, the observed number of alleles per locus ranging from 1.43 to 1.60, and percentage of polymorphic loci (PPL) ranging from 43.33 to 60.00.%. The levels of genetic variation were considered as moderate for all populations (He range from 0.1603 to 0.1956) and the the mean level of genetic diversity between population (Gst) was 0.3005. Cluster analysis and Principal Coordinates showed three main groups, the first group consists of 4 populations i.e Bandung, Kuningan,Purwakarta and Megamendung, the second was Sukaraja and the third was Sumedang. Based on Analysis of Molecular Variance (AMOVA), the Percentages of Molecular Variance within population (69%) is higher than that of between populations (31%). The moderate level of genetic variation in the community plantation forests, might be due to small population size, leading to reduce genetic variability. Further analysis is required to confirm this findings using other genetic marker.